Pengembangan Perangkat Pembelajaran Fisika Berbasis Model Problem Based Learning Berbantuan Simulai PhET untuk Meningkatkan Pemahaman Konsep Peserta Didik - Sri Ainun Wahyuni; I Wayan Gunada; Gunawan Gunawan; Jannatin 'Ardhuha (Kappa Journal, 2022)
This development research aimed to create physics learning tools based on problem based learning model using PhET simulation that are feasible, practical and effective to improve students' conceptual understanding. This research is a Research and Development (R&D) using 4D model developed by Thiagarajan (1974) which is consisted of define, design, develop, and disseminate. The learning tools being developed were syllabus, lesson plan, material, students' worksheet, and instrument of concept comprehension. The results of product validity developed as a whole from expert validators and practitioners have a very valid and reliable category with an average percentage above 75%, so it can be said to be feasible. The results of the practicality of the product developed of a teacher and student response questionnaire have a very practical category. The results of the N-Gain test for understanding the physics concepts of students obtained a moderate improvement category and were included in the quite effective category. So it can be conluded that the resulting development product is feasible, very practical and effective enough to improve students’ understanding of physics concepts.